PEMBULATAN BIAYA SEWA WARNET DALAM PANDANGAN FIQH PADA UNIT JASA LAYANAN INTERNET (UJLI) DI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO - Misbahul Ali (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
Abstract: Every human being needs wealth to fulfill his life needs. One of the efforts to fulfill his needs is by working. Leasing is a business that is often done by people to get a profit. So the practice of rounding the UJLI cafe rental fee is carried out when consumers want to rent a computer, a transaction is carried out first, namely by paying Rp. 2,000, - the use of the computer can be used for 30 minutes, then the use is still short or has not reached the usage limit, the payment is still rounded up to Rp. 2,000, - without the consent of the consumer. In the rounding process, when viewed in terms of the contract made in the lease transaction at the internet cafe, it is in accordance with the pillars of ijarah because the practice of internet services is carried out by two people who have a contract, ijab and qabul, wages and benefits of goods. However, on the terms of ijarah there is something that is not fulfilled, namely the principle of taradin, because there is no prior confirmation to the service user that has been used. So there is one party who feels aggris